Millennial students in fieldwork: Guidelines to success. A guide for allied health students and clinical educators involved in fieldwork - Quail, Michelle; Brewer, Margo; Briggs, Jillian; Colliver, Jessica; Dalby, Jen; Dawes, Emily; Flavell, Helen; Gilbert-Hunt, Susan; Hunter, Sally; Keys, Joshua; Lynch, Annique; McCallum, Amanda; et al. (Curtin University, 2018)
Universities, students, and employers have been reported to “...live in parallel universes” due to a lack of shared expectations (Mourshed, Farrell, & Barton, 2012, p.18). Therefore, it is not surprising that anecdotal reports of a gap between the expectations and preferences of current university students and the staff involved in their fieldwork education have been raised with and by Curtin University staff. The majority of students currently attending university have been classified as ‘millennials’. To optimise millennial students’ learning and transition to practice – be that through fieldwork placements or entry into the workforce – all staff involved in the education of millennial students need to understand the attitudes, values, and preferences of this population. While millennials are the most studied generation to date (National Chamber Foundation, 2012), minimal literature exists which has explored millennial students within the context of fieldwork. To address this gap, the overarching aim of this project was to gain an increased understanding of allied health millennial students to facilitate their engagement, learning, and hence success within placements and ultimately enhance their employability in the 21st Century workplace. Following a scoping review of the literature, focus groups with millennial students, millennial clinical educators and non-millennial clinical educators were held in July and August, 2017. Participants represented a range of allied health disciplines, including physiotherapy, speech pathology, nursing, and radiation therapy.